El teletrabajo como medio para la construcción de un Perú resiliente: Legislación regional comparada - Aranibar Ramos, Edgar Romario (2021)
During the economic crisis, consequence of coronavirus crisis, teleworking resurfaced such as a support for economies, provoking that some countries had to create or adequate a new legal figure to properly allow a large percentage of workers to carry out their duties without the need of presence. In this way, the relevance of teleworking for the economy and the need to internalize the existing technical-legal basis in the field is understood. Thus, the present research aims to analyze the development of teleworking at the domestic level -provision of paid services through the employment of TIC-, from a perspective of legislation and administration compared to South American countries, which maintain a close reality to Peruvian: Colombia, Argentina, Chile and Brazil. Obtaining information from secondary sources through bibliographic review in government and academic repositories. Noting, then, different conceptions across the countries for the understanding and regulation of teleworking -existent confusion between teleworking and remote work. At the domestic level, a legal advance is perceived where laws strengthened by necessity are contemplated; although, where a favor is perceived.